Flow cytometry‐based TCR‐ligand Koff‐rate assay for fast avidity screening of even very small antigen‐specific T cell populations ex vivo. Issue 9 (26th August 2016) - Nauerth, Magdalena; Stemberger, Christian; Mohr, Fabian; Weißbrich, Bianca; Schiemann, Matthias; Germeroth, Lothar; Busch, Dirk H.
Abstract: High epitope‐specific sensitivity of CD8 + T cells is required for optimal immune protection against intracellular pathogens as well as certain malignancies. The quality of antigen recognition of CD8 + T cells is usually described as "avidity" to its cognate peptide MHCI complex. T cell avidity is mainly dependent on the structural qualities of the T cell receptor (TCR), as convincingly demonstrated by recombinant TCR re‐expression experiments. Based on reversible MHCI multimer staining and k off ‐rate measurements of monomeric peptide MHCI complexes, we recently established a microscopic assay for determining the structural avidity of individual CD8 + T cells. Here we demonstrate that this assay can be adapted for rapid flow‐cytometric avidity screening of epitope‐specific T cell populations. Furthermore, we show that—in combination with conventional nonreversible MHCI multimer staining—even very small epitope‐specific CD8 + T cell populations can be analyzed directly ex vivo without the need for previous TCR cloning or T cell sorting. This simplified approach provides highly accurate mean TCR‐ligand k off ‐rate values for poly‐ or oligoclonal T cell populations and is ideally suited for high‐throughput applications in basic research as well as clinical settings. © 2016 International Society for Advancement of Cytometry